Dynamic crack propagation in a heterogeneous ceramic microstructure, insights from a cohesive model. (15th April 2015) - Taheri Mousavi, S.M.; Richart, N.; Wolff, C.; Molinari, J.F.
Abstract: A 2D plane-strain dynamically propagating crack under tensile loading is simulated with cohesive elements. Information of the main crack is extracted from a diffuse crack network with the use of graph properties. Micro-transgranular fracture properties are calibrated by comparing the crack path transgranular fracture percentage of numerical simulations with experimental data. Results show that although weaker grain boundaries cause more deflections in the crack path and consequently increase the crack length and roughness, the overall toughness is decreased due to reduction of transgranular fracture. The main crack failure mode transition at grain boundaries is compared to static (Hutchinson and Suo, 1992) and dynamic (Xu et al., 2003) classical analytical predictions. It is observed that in many cases, before the arrival of a transgranular fracture at a grain boundary, a micro-daughter crack starts to propagate on the interface. The crack tip extension through this daughter crack/mother crack mechanism complicates the interpretation of the main crack speed in dynamic regime. Yet, the dynamic analysis brings a more accurate prediction of the crack path in microstructures compared to the static one when the data are segregated according to this mechanism.